Legal Analysis of the Judge's Decision on the Implementation of Article 93 Paragraph 1 Based on Law No. 45 of 2009 Concerning Fisheries (Decision Study No. 317/Pid.Sus/2013/PU. RHL) - Henryco Siahaan; Ahmad Ansyari Siregar; Nimrot Siahaan; Bernat Panjaitan (International Journal of Science and Environment (IJSE), 2026)
This study aims to analyze the application of Article 93 paragraph (1) of Law No. 45 of 2009 concerning Fisheries in Decision No. 317/Pid.Sus/2013/PN.RHL. The focus of the study is on proving the elements of the crime, the suitability of the evidence used, and the judge's legal considerations in issuing the decision. The method used is normative legal research with a statutory approach and a case approach. The results of the study indicate that all elements of the crime regulated in Article 93 paragraph (1) have been fulfilled through valid evidence based on Article 184 of the Criminal Procedure Code. The judge in this case is considered to have applied the provisions of the article appropriately, both in terms of evidence and legal considerations. However, the decision still has weaknesses in terms of strengthening ecological aspects and deterrent effects on perpetrators of fisheries crimes. Therefore, a more comprehensive legal approach is needed that not only provides criminal sanctions, but also considers environmental losses and the need for sustainable protection of marine resources.